From particle ontology to formal causality: a hylomorphic reinterpretation of quantum entanglement - Lombardi, Sofía (2025)
This article addresses the reinterpretation of quantum entanglement from a neo-Aristotelian hylomorphic ontology, in which the global state of a composite system is conceived as the substantial form that actualizes its parts, and these parts possess determinate existence only within the whole on which they depend. It is assumed that classical atomistic reductionism, insofar as it treats matter as a passive aggregation of independent, localizable particles, cannot account for the non-separability and indivisibility of the quantum state that contemporary physics has documented from the Einstein-Podolsky-Rosen thought experiment to the experimental violations of Bell's inequalities. It is therefore argued that entanglement should not be interpreted as a causal interaction at a distance between previously complete entities, but rather as the empirical manifestation of a formal, downward causality that ontologically articulates the parts from the whole. The article draws on the metaphysical program developed by Robert Koons and William Simpson, in which matter is redefined as indeterminate potentiality and form as an irreducible structuring principle, a distinction that makes it possible to separate mere mechanical aggregates from genuinely holistic compound substances.